Response Surface Methodology-Based Parameter Optimization of Candlenut Seeds Extraction (Aleurites moluccana Willd) - Yeni Variyana; Dewi Ermaya; Shintawati Shintawati; Devy Cendekia; Mahfud Mahfud (Program studi Teknik Kimia UNS, 2023)
Abstract. Aleurites moluccana Willd, known candlenut plant, has the potential to be used for vegetable oil, pharmacological purposes, and biofuel. However, there is a lack of knowledge on the optimal extraction conditions for this extraction. The current study aimed to use response surface methodology (RSM) to optimize the Microwave Hydrodiffusion Gravity (MHG) conditions for extraction yield. A three-factor-three-level Box-Behnken design (BBD) was used to investigate the effects of three independent parameters: material size (A), microwave power (B), and extraction time (C). The experimental data for the candlenut seed extraction were analyzed to obtain quadratic polynomial equations. The effects of various parameters on the yield of extraction yield were then examined and analyzed using plots and contours.The results showing extraction yield significantly influenced all independent parameters were p < 0.0001. Further, The study predicted the optimum conditions for extracting candlenut seeds, which included using material size in 1.378 cm, microwave power of 599.359 W, and extraction time 66.076 min, resulted yield of 5.015%. Based on experimental data conditions, the highest extraction yield was 5.5% of 1 cm, 600 W, and 60 min, respectively, which were in good agreement with the predicted model. The study concluded that the optimized MHG method could be useful in industrial extraction processes and the use of statistical method can optimize the extraction process and reduce the number of experiments required.Keywords:Candlenut, RSM, MHG, yield